(untitled) (Research, Society and Development, 2021)
Objective: Evaluate the effects of non-thermal plasma therapy (NTP) for the treatment of diabetic foot injuries in two patients, considering the evolution of the steps of the healing process, pain sensitivity, and quality of life. Methodology: Lesions in the lower limbs of two patients with Diabetes mellitus (DM) with similar anatomical location and dimensions were treated, one patient with controlled DM and the other classified as uncontrolled DM. The application of NTP was performed for 10 minutes, 3 times a week in direct contact with the lesions. The same protocol was applied in both clinical cases to allow a reliable evaluation of the healing process. Results and Discussion: The lesions presented progressive regression until their complete regeneration (100%), without the development of infections during treatment. Conclusion: The results obtained in the two clinical cases allow us to attest that the NTP application in the treatment of diabetic foot injuries resulting from DM constituted an important therapeutic tool for the evolution of the healing process of these injuries, with a significant reduction in the lesion area in a short period of time. The definition of the ideal treatment protocol depends on the expansion of the number of studies and the increase of the studied population.